Peran Ayah Terhadap Kematangan Emosi Mahasiswa STIKES Husada Mandiri Poso - SUFYANINGSI, ULFA (Journal of Health Education and Literacy, 2024)
Emotional maturity is an important factor for prospective nursing students in dealing with pressure and situations that demand empathy for patients. This study aims to determine the relationship between father's role and emotional maturity of prospective nursing students at STIKES Husada Mandiri Poso. This study used an analytic design with a cross-sectional approach. The study sample amounted to 51 students selected using proportional random sampling technique. Data were collected through questionnaires measuring father's role and emotional maturity, and the data were analyzed using the Pearson correlation test. The results showed that there was a significant relationship between father's role and emotional maturity of prospective nursing students, with a correlation value of 0.437 (p < 0.05). This shows that the higher the father's role in supporting his child, the higher the level of emotional maturity of the student. In conclusion, the role of fathers has a positive influence on the emotional maturity of prospective nursing students, which in turn can improve the quality of care provided to patients. This study recommends the importance of increasing father's involvement in supporting students' emotional development.